Murine cytomegalovirus infection leads to increased levels of transplant arteriosclerosis in a murine aortic allograft model - Heim, Christian; Abele-Ohl, Silke; Eckl, Sebastian; Ramsperger-Gleixner, Martina; Mahmoudian, Shohreh; Weyand, Michael; Stamminger, Thomas; Ensminger, Stephan M. (Transplantation, 2010)
Introduction. Cytomegalovirus infection after heart transplantation is considered as risk factor for the development of transplant arteriosclerosis. Therefore, the aim of this study was to investigate the effect of murine cytomegalovirus (MCMV) as a single risk factor on transplant arteriosclerosis in an experimental aortic allograft model. Methods. Major histocompatibility complex class I-mismatched aortas of C.B10-H2(b)/LilMcdJ donor were transplanted into BALB/c recipients, which were either mock-infected or infected with MCMV (strain Smith) on day 7 and harvested 37 days after transplantation. In one experimental group animals received a daily dose of everolimus to increase the viral load of recipients. Grafts were analyzed by histology, morphometry, and immunofluorescence. Intragraft cytokine mRNA production was analyzed by real-time polymerase chain reaction (PCR), and persistence of cytomegalovirus infection was confirmed by TaqMan PCR. Results. After infection with MCMV, there was significantly more intimal proliferation when compared with uninfected controls (intimal proliferation 83.5%±9.6% [MCMV+] vs. 43.9%±5.1% [MCMV+]), indicating that MCMV plays a role in the development of transplant arteriosclerosis. Even after treatment with everolimus, MCMV infection pronounced significantly more intimal proliferation (intimal proliferation 52.5%±7.3% [MCMV+] vs. 20.2%±1.7% [MCMV+]). Intragraft mRNA expression showed significantly higher production of CD62E, intercellular adhesion molecule-1, and vascular cell adhesion molecule-1 after infection with MCMV. Cellular infiltration revealed significantly more CD4+, CD8+, and dendritic cells. We could also confirm the presence of MCMV for the duration of the experimental protocol by PCR within the spleen, liver, salivary glands, lung, and the aortic transplant. Conclusion. These data suggest that MCMV infection plays an important role in the development of transplant arteriosclerosis. © 2010 by Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Adhesion molecules; Dendritic cells; Murine cytomegalovirus; Transplant arteriosclerosis